Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1001/jamasurg.2019.5087
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and Health Care Utilization Among Medicare Patients Undergoing Emergency General Surgery vs Those With Acute Medical Conditions

Abstract: IMPORTANCE Emergency general surgery (EGS) represents 11% of hospitalizations, and almost half of these hospitalized patients are older adults. Older adults have high rates of mortality and readmissions after EGS, yet little is known as to how these outcomes compare with acute medical conditions that have been targets for quality improvement. OBJECTIVE To examine whether Medicare beneficiaries who undergo EGS experience similar 1-year outcomes compared with patients admitted with acute medical conditions. DESI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 53 publications
0
24
0
1
Order By: Relevance
“…Until recently patients undergoing emergency general surgery including emergency laparotomy have been a relatively overlooked group [ 15 ]. Just under a decade ago, major cohort studies reported 30-day mortality for emergency laparotomy of between 14 and 18.5% rising to over 25% in patients over 80 years of age [ 14 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Until recently patients undergoing emergency general surgery including emergency laparotomy have been a relatively overlooked group [ 15 ]. Just under a decade ago, major cohort studies reported 30-day mortality for emergency laparotomy of between 14 and 18.5% rising to over 25% in patients over 80 years of age [ 14 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…1 For those who survive the index hospitalization, more than half are rehospitalized in the year after discharge, and one in three die. 1 Although surgical quality improvement initiatives have largely focused on reducing complications and mortality in the acute perioperative period, 2 patients' long-term needs beyond this 30-day window remain understudied and the lived experience from the patient perspective poorly understood. To address this gap, we qualitatively explored factors contributing to or impeding recovery as experienced by older adults 3 months post-EGS.…”
Section: Introductionmentioning
confidence: 99%
“…Older adults have accompanying co‐morbidities that place them at significantly higher risk of postoperative mortality, morbidity, use of intensive care resources and a longer hospital stay after emergency surgery 4–8 . It is becoming increasingly important to formally assess elderly patients for challenges to their functional status due to frailty 9–11 . Frailty is a measure of increased vulnerability and decreased physiological reserve to stressors, such as surgery, which impairs recovery and return to preoperative functional level 12,13 .…”
Section: Introductionmentioning
confidence: 99%